Entropy Solutions for Nonlinear Elliptic Anisotropic Homogeneous Neumann Problem. (3rd April 2013) - Bonzi, B. K.; Ouaro, S.; Zongo, F. D. Y.
Abstract : We prove the existence and uniqueness of entropy solution for nonlinear anisotropic elliptic equations with Neumann homogeneous boundary value condition forL 1 -data. We prove first, by using minimization techniques, the existence and uniqueness of weak solution when the data is bounded, and by approximation methods, we prove a result of existence and uniqueness of entropy solution.